Digital communication competence and technology adoption: Drivers of performance among small-scale millennial farmers in Indonesia - Sasmita, Hari Otang; Saleh, Amiruddin; Priatna, Wahyu Budi; Muljono, Pudji (Edelweiss Applied Science and Technology, 2024)
Digital development in rural areas has become a driving force in increasing agricultural and rural economic productivity. However, the lack of digital communication competence among farmers remains a problem, causing market information asymmetry and an inability to effectively utilize information and communication technology (ICT) in the agricultural sector to increase business profits. Therefore, it is important to examine the use of ICT in the agricultural sector in 19- to 39-year-old age groups (or millennial farmers), as this generation is considered closest to digital technology. This study used a survey method with 345 millennial farmers in Bogor, Indonesia, and data were analyzed using partial least squares-structural equation modeling (PLS-SEM). The results of this study indicate that digital communication competence, as reflected by motivation, knowledge, and digital skills, plays a crucial role in enhancing the performance of millennial farmers both directly and indirectly through ICT utilization. Farmers possessing superior digital communication competencies exhibit a greater inclination to employ technology for communication, information acquisition, idea dissemination, and marketing in their agricultural pursuits, resulting in more informed decision making and potentially improved productivity and profitability. The results contribute to the understanding of the role of digital communication competence and ICT utilization in enhancing farmers’ performance.